2014
DOI: 10.4103/0259-1162.128921
|View full text |Cite
|
Sign up to set email alerts
|

Transient aphonia, aphagia and facial tingling following intrathecal administration of fentanyl

Abstract: Subarachnoid block with local anaesthetic agent and opiod as an adjuvant is a well-known technique with a good record of safety. However, some rare neurological complications like aphonia, dysphagia and tingling sensation have been reported following their administration in pregnant females posted for labour analgesia or caesarean section. We report a case of transient aphonia, aphagia and facial tingling following intrathecal administration of bupivacaine along with fentanyl for lower limb wound debridement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Interestingly, the presentation of these mentioned cases had a variety of presentations, and the duration of recovery was also varied. Though the risk factors, age between 10 and 35 years of age and female gender are present in our case, her lack of similar history in the past, good educational background with school level education, and good socioeconomic status make this diagnosis unlikely 3,4,7 …”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Interestingly, the presentation of these mentioned cases had a variety of presentations, and the duration of recovery was also varied. Though the risk factors, age between 10 and 35 years of age and female gender are present in our case, her lack of similar history in the past, good educational background with school level education, and good socioeconomic status make this diagnosis unlikely 3,4,7 …”
Section: Discussionmentioning
confidence: 75%
“…The most likely mechanism is due to the rostral spread of the drug to the speech area or cranial nerves, and the transient nature of the symptom is due to the rapid clearance of the drug from the CSF 12 . Studies have shown cases where aphonia alone or accompanied by neurological symptoms have occurred after spinal anesthesia in pregnant females and other surgeries 1,7,11,12 . However, no opioid was used in this case, excluding it as a cause of aphonia.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Gupta et al . [ 2 ] reported aphonia and aphagia in a male patient posted for lower limb debridement at 3 min after receiving 12.5 mg heavy bupivacaine with 25 μg fentanyl intrathecally which recovered spontaneously in 10-15 min. In both cases the authors believe extensive cephalad spread of fentanyl through the Cerebrospinal fluid (CSF) as the cause for neurological symptoms.…”
mentioning
confidence: 99%